PEMBUATAN APLIKASI SISTEM UJIAN ONLINE PADA SMK GARUDA NUSANTARA BEKASI - Riyadi, Ahmad; Hermaliani, Eni Heni; Utami, Dwi Yuni (Jurnal Ilmiah SINUS, 2019)
Exam is one way to evaluate the learning process and is a medium to make measurements on the ability of students in a field of study. The school exams at SMK Garuda Nusantara Bekasi are still paper based, using paper for either the test booklet or the answer sheet. This paper based test for surely resulted in high monetary budget and inefficiency of correcting time. Due to this condition, the writer decided to create an online exam system application to make the implementation and test data processing easier either for the students or the teacher. The method of research used in this study was software development, especially the waterfall and data collection techniques by making direct observations about the process of running the school exams and interviewing the school community. The results of the study were in the form of analysis, design and implementation of online exam system applications using the PHP programming language with MySQL database processing. The application has made significant impact on the increasing of the teaching and learning process effectiveness. In addition, it also increases the management value it can be done online using internet technology.